Мистецтво концертмейстера: творчий і педагогічний аспект діяльності - Коцюрба, Наталія Євгеніївна; Дуда, Світлана Леонідівна; Kotsiurba, Nataliia Ye.; Duda, Svitlana L. (Центр міжнародного наукового співробітництва, 2019)
The creative activity of a pianist-concertmaster includes pedagogical and organizational aspects along with performing and is therefore unique in its multifunctionality. Nowadays concertmaster's activity of a pianist, having absorbed the empirical experience of several generations of musicians, has become particularly widespread both in artistic and pedagogical practice. Professional concertmasters are an important link in the complex chain of musical-educational process. The essence of their work is to provide their partner (partners) with artistic creativity using musical accompaniment, and moreover – to establish a close relationship between the elements included in the concepts of "concertmaster" and "teacher". Such aspect of the study determines the relevance of the topic "The art of being a concertmaster: creative and pedagogical aspects of the activity". The article examines the art of being a pianist-concertmaster, the peculiarities and specificity of its functioning; it analyzes the pedagogical aspect of concertmaster's work and defines the role of concertmasters in the process of musical and pedagogical education; it determines the features of the concertmaster's collaboration with the soloist and the role of the concertmaster for the successful formation of the future professional musician. Творча діяльність концертмейстера-піаніста – виконавська, педагогічна, організаційна – унікальна своєю багатофункціональністю. Сьогодні концертмейстерська діяльність піаніста, увібравши емпіричний досвід кількох поколінь музикантів, отримала особливо широке поширення як в художній, так і в педагогічній практиці. Професійний концертмейстер - важлива ланка в складному ланцюжку музично-освітнього процесу. Суть його роботи полягає в забезпеченні художньої творчості партнера (партнерів) за допомогою музичного супроводу, і більше того – встановлення тісного взаємозв'язку елементів, що входять в поняття «концертмейстер» і «педагог». Такий аспект дослідження зумовлює актуальність теми «Мистецтво концертмейстера: творчий і педагогічний аспект діяльності». У статті досліджено мистецтво піаніста-концертмейстера, його особливості та специфіка функціонування; проаналізовано педагогічний аспект концертмейстерської роботи, зазначено роль концертмейстера в процесі музичного та педагогічного виховання; визначено особливості співпраці концертмейстера з солістом та значення ролі концертмейстера для успішного становлення майбутнього професійного музиканта.
The art of being a concertmaster: creative and pedagogical aspects of the activity
Keywords: musical performance; artistic thinking; development and formation of personality; acquisition of knowledge; skills and abilities; музичне виконавство; художнє мислення; розвиток особистості; набуття вмінь; навичок